Reflections on fiscal coordination and integration in Europe - Gong Cheng; Kari Korhonen (Asian Development Bank Institute (ADBI), 2020)
This paper provides an overview of the key steps that were made in the European Union toward enhancing fiscal policy coordination and integration prior to the Covid-19 crisis. It especially highlights the key challenges and strategies that should be considered when thinking of further fiscal integration in the monetary union. Compared to economic and financial integration, fiscal integration would require much stronger political support. Fiscal integration is not meant to be achieved overnight but it should take a stepwise approach, which could encompass policy coordination, pooling resources for macroeconomic stabilization and fiscal backstops, debt mutualization and safe assets, and ultimately a common budget. This paper also aims to provide some inspiration for East Asian economies when they consider strengthening fiscal integration in their region. Despite some fundamental differences between Asian and European economies, there are common issues that must be tackled.
Keywords: E62; E63; F55; F62; F63; 330; economic integration; fiscal integration; fiscal capacity; safe assets; sovereign debt; backstops; policy coordination